Answer:
r is usually the radius but can also be a variable, in this case r = -189
Explanation:
Solve for r:
-13 = r/9 + 8
Put each term in r/9 + 8 over the common denominator 9: r/9 + 8 = r/9 + 72/9:
-13 = r/9 + 72/9
r/9 + 72/9 = (r + 72)/9:
-13 = (r + 72)/9
-13 = (r + 72)/9 is equivalent to (r + 72)/9 = -13:
(r + 72)/9 = -13
Multiply both sides of (r + 72)/9 = -13 by 9:
(9 (r + 72))/9 = -13×9
(9 (r + 72))/9 = 9/9×(r + 72) = r + 72:
r + 72 = -13×9
9 (-13) = -117:
r + 72 = -117
Subtract 72 from both sides:
r + (72 - 72) = -72 - 117
72 - 72 = 0:
r = -72 - 117
-72 - 117 = -189:
Answer: r = -189